20 postgraduate students lead the new leadership of UMPSA PGA - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2024)
KUANTAN, 5 April 2024 – A total of 20 postgraduate students from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) have been appointed and entrusted to lead the new leadership of the UMPSA Postgraduate Association (PGA) in 2024.